New ionic cobalt(iii) complexes based on the N, N-bis(2-pyrazinecarboxamide)-1, 2-benzene ligand: application to the formation of organic carbonates from epoxides and CO2. (21st October 2015) - Adolph, Michael; Zevaco, Thomas A.; Altesleben, Christiane; Staudt, Simone; Walter, Olaf; Dinjus, Eckhard
Abstract : New cobalt(iii ) complexes based on N, N -bis(2-pyrazine-carboxamide)-1, 2-benzene were tested as catalysts for the coupling of propylene- and cyclohexene oxide with CO2 . Abstract : In this contribution, we report a further development within an "open" N4 -ligand class obtained via condensation of 1, 2-ortho-phenylene diamine with nitrogen-containing carboxylic acids. N, N -Bis(2-pyrazinecarboxamide)-1, 2-benzene reacted with different cobalt precursors to form new ionic Co(iii ) complexes in good yields. These compounds were successfully tested as potential catalysts for the coupling of epoxides with carbon dioxide.